Effect of 6-Methoxybenzoxazolinone on the Cecal Microbiota of Adult Male Brandt’s Vole - Dai, Xin; Chen, Lin; Liu, Mengyue; Liu, Ying; Jiang, Siqi; Xu, Tingting; Wang, Aiqin; Yang, Shengmei; Wei, Wanhong (Frontiers in Microbiology, 2022)
The anti-microbial effects of plant secondary metabolite (PSM) 6-methoxybenzoxazolinone (6-MBOA) have been overlooked. This study investigated the effect of 6-MBOA on the cecal microbiota of adult male Brandt’s voles, to evaluate its effect on the physiology of mammalian herbivores. The growth of voles was inhibited by 6-MBOA. A low dose of 6-MBOA enhanced the observed species, as well as the Chao1 and abundance-based coverage estimator indices and introduced changes in the structure of cecal microbiota. The abundance of the phylum Tenericutes, classes Mollicutes and Negativicutes, order Selenomonadales, families Ruminococcaceae and Veillonellaceae, genera Quinella, Caproiciproducens, Anaerofilum, Harryflintia, and unidentified Spirochaetaceae in the cecal microbiota was enhanced upon administration of a low dose of 6-MBOA, which also inhibited glucose metabolism and protein digestion and absorption in the cecal microbiota. 6-MBOA treatment also stimulated butyrate production and dose-dependently enhanced the metabolism of xenobiotics in the cecal microbiome. Our findings indicate that 6-MBOA can affect Brandt’s voles by inducing changes in the abundance of cecal bacteria, thereby, altering the contents of short-chain fatty acids and pathway intermediates, ultimately inhibiting the growth of voles. Our research suggests that 6-MBOA could potentially act as a digestion-inhibiting PSM in the interaction between mammalian herbivores and plants.